Risk factors for community-associated multidrug resistant Pseudomonas aeruginosa in Veterans with spinal cord injury and disorder: a retrospective cohort study - Kale, Ibuola O. (Spinal Cord, 2017)
STUDY DESIGN: Retrospective cohort study OBJECTIVES: To identify independent risk factors associated with community-associated multidrug resistant P. aeruginosa (MDRPA) in a population of Veterans with spinal cord injury and disorders (SCI/D). SETTING: 127 Veterans Affairs healthcare facilities METHODS: Laboratory results from January 1, 2012 to December 31, 2013 were collected and MDRPA cultures were compared to non-MDRPA cultures. RESULTS: One thousand four hundred forty one cultures were collected from Veterans with SCI/D, including 227 cultures with MDRPA isolates. Characteristics associated with an increased odds of MDRPA include age 50-64 (aOR= 1.80, 95% CI= 1.13-2.87), MDRPA culture in the past 365 days (aOR= 9.12, 95% CI= 5.88-14.15), and carbapenem exposure in the past 90 days (aOR= 2.56, 95% CI= 1.35-4.87). In contrast, paraplegia was associated with a 53% decreased odds of MDRPA compared to those with tetraplegia (aOR= 0.47, 95% CI= 0.32-0.69). CONCLUSIONS: Risk factors for community-associated MDRPA include prior history of MDRPA and exposure to carbapenems. Awareness of these factors is important for targeted prevention and treatment of MDRPA in patients with SCI/D.